The Influence of Arts Participation on Subjective Well-Being, Emotional Regulation as a Mediator - Tianyu, Wang; Alexander, Chelum (Frontier Scientific Publishing Pte. Ltd., 2025)
This study examined whether arts participation (AP) predicts subjective well-being (SWB) among Chinese undergraduates and whether emotional regulation (ER) mediates this relationship. A cross-sectional survey of 215 students in Shandong showed that AP significantly predicted SWB both directly and indirectly through ER, confirming partial media tion. Findings suggest that arts engagement enhances well-being partly by improving emotional regulation, highlighting the value of integrating arts modules, creative labs, and emotion-regulation workshops into university programs. Limitations include the cross-sectional design, self-report data, single-province sample, and potential self-selection bias. Future research should use longitudinal or experimental designs, broader samples, and explore additional mediators and moderators.